Animal dice adios - Gikow, Louise; Brannon, Tom (Mexico : Sitesa, 1989)
Baby Kermit's plans to make Baby Animal take a nap meet with resistance as Baby Animal insists on taking imaginary trips on a boat, in a balloon, and to an amusement park
Translation of: Animal go bye-bye